Island Africa and vertebrate evolution: a review of data and working hypotheses - (:unkn) unknown (My University, 2020)
From mid-Cretaceous to Early Miocene, Africa was geographically isolated as agigantic island, the Island Africa. This considerably impacted local evolution of continentalvertebrates. The native fauna of the Island Africa is and was depauperate for poorly known reasons. Although an Island, Africa was intermittently connected to Laurasia bydiscontinuous routes across the Neo-Tethys. Owing to these routes, various allochthonous groups of Eurasian origin entered Africa where they found favorable evolutionary conditions with relaxed competitive pressure; many of these groups evolved successfully, giving rise to new African clades and important endemic radiations. Thus, Island Africa acted as a secondary cradle, boosting the evolution of stem groups of Eurasian origin. Notably, all Cenozoic African mammals likely derived from stem groups of Laurasian origin. A remarkable number of endemic African lineages evolved successfully in extant African faunas, and even colonized several continents. They survived in particular the Miocene event of the Great Old World Interchange. The earlier faunal relations of Africa and Eurasia across the Tethys likely contributed to the success of the endemic African evolution.
Keywords: African Research